MacGyver Season 7 Disc 1 - Anderson, Richard Dean.; Paramount Television; Paramount Home Entertainment (Firm); CBS DVD (Firm) (Hollywood, Calif. : Paramount Home Entertainment, 2006)
The final season finds MacGyver facing off against nuclear terrorists, a mad arsonist, and a voodoo priest, plus a time travel adventure and an emotional series finale.
Honest Abe -- The 'hood -- Obsessed -- The Prometheus syndrome.
Title from container.
Originally broadcast on television during the 1991-1992 season.
Richard Dean Anderson.
Not rated.
DVD, region 1, full screen presentation; Dolby Digital stereo.
Closed-captioned.
Keywords: Government missions, American -- Drama; Technology -- Drama; Action and adventure television programs; Drama; Video recordings for the hearing impaired; Adventure television programs